2010
DOI: 10.1101/gad.1972310
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRA gene rearrangements are frequent genetic events in PDGFRA-amplified glioblastomas

Abstract: Gene rearrangement in the form of an intragenic deletion is the primary mechanism of oncogenic mutation of the epidermal growth factor receptor (EGFR) gene in gliomas. However, the incidence of platelet-derived growth factor receptor-a (PDGFRA) gene rearrangement in these tumors is unknown. We investigated the PDGFRA locus in PDGFRA-amplified gliomas and identified two rearrangements, including the first case of a gene fusion between kinase insert domain receptor (KDR) (VEGFRII) and the PDGFRA gene, and six ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 35 publications
3
152
3
2
Order By: Relevance
“…PDGFR is mutated in up to 30% of GBMs, 5 and the PDGFRAD8,9 isoform (with a deletion of exons 8 and 9) results in constitutive activation and is seen in 40% of GBMs. 35 In a recent study, PDGFRA amplification was seen in 23% of GBM cases and demonstrated a significant reduction in median survival in only the IDH1 mutation subgroup (16.0 vs 72.6 months). 38 Despite the importance of PDGF in GBM proliferation-as it is found upstream of important signaling pathways such as AKT, involved with in vitro growth of GBM, and used in animal models of GBM-no definitive role in predicting prognosis has been seen in clinical studies.…”
Section: Platelet-derived Growth Factor Receptor (Pdgfr)mentioning
confidence: 99%
“…PDGFR is mutated in up to 30% of GBMs, 5 and the PDGFRAD8,9 isoform (with a deletion of exons 8 and 9) results in constitutive activation and is seen in 40% of GBMs. 35 In a recent study, PDGFRA amplification was seen in 23% of GBM cases and demonstrated a significant reduction in median survival in only the IDH1 mutation subgroup (16.0 vs 72.6 months). 38 Despite the importance of PDGF in GBM proliferation-as it is found upstream of important signaling pathways such as AKT, involved with in vitro growth of GBM, and used in animal models of GBM-no definitive role in predicting prognosis has been seen in clinical studies.…”
Section: Platelet-derived Growth Factor Receptor (Pdgfr)mentioning
confidence: 99%
“…One of them, the most significant one regarding GBM, is PDGFRA. The other isoform is also PDGFRAD (with a deletion of exons 8 and 9), seen in 40% of GBMs, and leads to constitutive activation [14,15]. According to the Cancer Genome Atlas, PDGFRA has a crucial role in the proneural subtype of GBM; however, no changes were observed in prognosis of the evaluated patients [16].…”
Section: Proliferative and Antiproliferative Pathways And Their Rolesmentioning
confidence: 96%
“…Therefore, to better observe the cytoplasm of cells, we used fluorescent GFP protein that was encoded by the plasmid used to express the oncogene KP into NIH-3T3 cells (KP cells). 13 The resulting images taken at three different focal planes (3,8, and 14 mm), using the INCA3000, clearly show that the KPtransformed cells form transformed clusters with cells pilling up on top of each other (Fig. 1C, D).…”
Section: Imaging Cellular Clusters In 384-well Microtiter Platesmentioning
confidence: 99%
“…13 KP cells and the parental NIH-3T3 cells were cultured under a humidified atmosphere at 378C/5% CO 2 -95% air in complete Dulbecco's modified Eagle's medium (ATCC: ) containing 10% heat-inactivated calf serum (Colorado Serum Co.: CS1334), 100 units/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation